Globalization and the increase of human psychological problems: an effective remedy from religious perspectives / Abdul Latif Abdul Razak - Abdul Razak, Abdul Latif (2008)
Nowadays, the world in general is witnessing the frightening increase of psychological problems. This is due to the fast developmental changes brought by globalization and the marginalization of religion that place man in the state of difficulty and stress to cope with the changes. Secular and irreligious psychological approaches which reject the spiritual aspects of man could not serve as the proper solutions to the problems and are unable to instill the genuine states of tranquility in man. Religion with its beliefs and practices guarantees the best and effective solutions to the problems. The challenge is how to apply those religious beliefs and practices in remedying those psychological problems. Undoubtedly, this requires right understanding of religious concepts and principles and the internalizations of these principles into daily life. For this purpose, the paper begins with the discourse on the true understanding of the nature of man, his uniqueness compared to animal and his meaning and purpose of life. This true understanding of the nature of man leads to the understanding of the root causes of the problems and not the symptomatic ones. Consequently, the proper remedy can be given to cure these illnesses.